THE COURSE OF THE SENIOR SECONDARY STUDENTS IN SOME IDENTIFIED SCHOOLS IN THE MUNICIPALITY OF DAANBANTAYAN - Dato-on, Rowena P (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 3-4, 2008, 2008)
It was the main purpose of this study to look into the course preferences of the senior secondary students in some identified secondary schools in the municipality of Daanbantayan. To arrive at the profile of the socio-economic status of the parents, course preferences of the senior secondary students, and the reasons for choosing such courses, the researcher used the descriptive-normative survey method. On the treatment of data, percentage was used in determining the profile of the socio-economic status of the parents. For the course preferences, Raw Weighted Score (RWS) was employed and for the reasons why the respondents chose the course, ranking was used.